Defining and researching the concept of resilience in LGBT+ later life: Findings from a mixed study systematic review. - Anže Jurček; Brian Keogh; Greg Sheaf; Trish Hafford-Letchfield; Agnes Higgins (PLoS ONE, 2022)
Within the literature, resilience is described as either a trait, an outcome or a process and no universal definition exists. A growing body of research shows that older LGBT+ adults show signs of resilience despite facing multiple inequalities that negatively impact their health and social wellbeing. The aim of this review was to examine how resilience is defined in LGBT+ ageing research and how it is studied. A mixed-study systematic search of peer-reviewed research papers published before June 2022 was conducted using the electronic databases CINAHL, Embase, Medline, PsycInfo, Social Science Database and Web of Science. This resulted in the screening of 7101 papers 27 of which matched the inclusion criteria. A quality appraisal was conducted using the Mixed Methods Appraisal Tool. Findings show that papers often lack a clear definition of resilience and application of resilience theory within the studies, although many of the papers conceptualised resilience as either a trait, process or an outcome. However, resilience was rarely the primary focus of the studies and was researched using a variety of measurement instruments and conceptual frameworks. Given the socioeconomic disparities, diverse social relations, histories of discrimination and stigma, and acts of resistance that have shaped the lives of older LGBT+ populations, resilience is a topic of growing interest for researchers and practitioners. Clear definitions of resilience and application of resilience theory could help improve methods used to study the concept and lead to more robust findings and the development of effective interventions. Greater clarity on the concept of resilience could also broaden the focus of research that informs policies and practice, and support practitioner training in resilience and the particular experiences of older LGBT+ adults.